Answer:
1) 2x-3 = x -3 + x
2) 2x - 6 = -6 + 2x
3) ![\frac{3}{5}-\frac{13}{5}=-6.9+4.9](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B5%7D-%5Cfrac%7B13%7D%7B5%7D%3D-6.9%2B4.9)
4) 3x+0 = 3x
5) ![\frac{5}{3}-x+\frac{1}{3}=-\frac{3}{2}x+2+\frac{1}{2}x](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B3%7D-x%2B%5Cfrac%7B1%7D%7B3%7D%3D-%5Cfrac%7B3%7D%7B2%7Dx%2B2%2B%5Cfrac%7B1%7D%7B2%7Dx)
Step-by-step explanation:
We need to match each expression on the left with an equivalent expression on the right
The expressions are equivalent if the have the same results.
1) 2x - 3
Looking at the options the best match is:
x -3 + x
When solve we get:
2x-3
So, 2x-3 = x -3 + x
2) 2x - 6
Looking at the options the best match is:
-6 + 2x
Because according to commutative property: a+b = b+a
So, 2x - 6 = -6 + 2x
3) ![\frac{3}{5}-\frac{13}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B5%7D-%5Cfrac%7B13%7D%7B5%7D)
First simplifying the given expression:
![\frac{3}{5}-\frac{13}{5}\\=\frac{3-13}{5}\\=\frac{-10}{5}\\=-2](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B5%7D-%5Cfrac%7B13%7D%7B5%7D%5C%5C%3D%5Cfrac%7B3-13%7D%7B5%7D%5C%5C%3D%5Cfrac%7B-10%7D%7B5%7D%5C%5C%3D-2)
Looking at the options, -6.9+4.9 = -2
So, ![\frac{3}{5}-\frac{13}{5}=-6.9+4.9](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B5%7D-%5Cfrac%7B13%7D%7B5%7D%3D-6.9%2B4.9)
4) 3x + 0
Looking at the options the best match is:
3x
Because, adding 0 in 3x will result in 3x
So, 3x+0 = 3x
5) ![\frac{5}{3}-x+\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B3%7D-x%2B%5Cfrac%7B1%7D%7B3%7D)
First simplifying:
![\frac{5}{3}-x+\frac{1}{3}\\=\frac{5-3x+1}{3}\\=\frac{6-3x}{3}\\= \frac{3(2-x)}{3}\\=2-x](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B3%7D-x%2B%5Cfrac%7B1%7D%7B3%7D%5C%5C%3D%5Cfrac%7B5-3x%2B1%7D%7B3%7D%5C%5C%3D%5Cfrac%7B6-3x%7D%7B3%7D%5C%5C%3D%20%20%5Cfrac%7B3%282-x%29%7D%7B3%7D%5C%5C%3D2-x)
Now, solving the option: ![-\frac{3}{2}x+2+\frac{1}{2}x](https://tex.z-dn.net/?f=-%5Cfrac%7B3%7D%7B2%7Dx%2B2%2B%5Cfrac%7B1%7D%7B2%7Dx)
![=\frac{-3x+4+1x}{2}\\=\frac{-2x+4}{2}\\=\frac{2(-x+2)}{2}\\=-x+2\\or\\=2-x](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-3x%2B4%2B1x%7D%7B2%7D%5C%5C%3D%5Cfrac%7B-2x%2B4%7D%7B2%7D%5C%5C%3D%5Cfrac%7B2%28-x%2B2%29%7D%7B2%7D%5C%5C%3D-x%2B2%5C%5Cor%5C%5C%3D2-x)
So, ![\frac{5}{3}-x+\frac{1}{3}=-\frac{3}{2}x+2+\frac{1}{2}x](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B3%7D-x%2B%5Cfrac%7B1%7D%7B3%7D%3D-%5Cfrac%7B3%7D%7B2%7Dx%2B2%2B%5Cfrac%7B1%7D%7B2%7Dx)